SOSIALISASI PEMANFAATAN LIMBAH TANAMAN BUNCIS (PHASEOLUS VULGARIS, L) SEBAGAI PUPUK CAIR DI DESA TONGKOK - Endang Lovisia; Merti Triyanti (JURNAL CEMERLANG: Pengabdian pada Masyarakat, 2021)
This community service activity is motivated by the large amount of waste from bean plants in Tongkok Village, Lahat Regency which has not been used optimally, especially as liquid fertilizer. Waste from the bean plant is disposed of, burned and not used . This causes a high volume of waste and environmental pollution. Therefore, the pkm stkip pgri lubuklinggau team tried to socialize the use of bean plant waste (phaseolus vulgaris, l) as liquid fertilizer in tongkok village. This PKM has been carried out by involving partners, namely the Tongkok village community and is enthusiastically followed. The output target to be achieved by the PKM team is to increase community values ​​and publications. In its implementation, it uses theoretical and practical methods starting from the preparation stage, providing materials and practices for making liquid fertilizer for bean plant waste